The Latham Technique - Belma Işık Aslan (Galenos Yayinevi, 2008)
The Latham technique is the initial interventional procedure used to treat the facial orthopedic problems found in unilateral (UCLP) or bilateral complete cleft lip and palate (BCLP) patients. In cleft lip and palate patients, the soft tissue and basal abnormalities may have a recognizable pattern of deformity defined by excess or deficiency in anatomic form, position or direction within the craniofacial milieu. The Latham appliance applies controlled directional forces to reposition the displaced basal segments and realign soft tissue margins before corrective surgery is performed. In UCLP and BCLP patients, the Latham technique induces profound and complex orthodontic changes and it does not harm facial skeletal growth.